Thermodynamic Analysis of Refrigerant Systems for Ethane Recovery and Helium Extraction in Medium-Pressure Natural Gas Processing - Hong Jiang; Wentang Huang; Xiang Cheng (Energies)
Based on the medium-pressure natural gas ethane recovery and helium extraction process, this paper proposes three different refrigerant Schemes. Thermodynamic analysis and adaptability evaluation of the three Schemes were conducted using Aspen HYSYS V12 software. The ethylene–propane cascade refrigeration Scheme demonstrated superior energy efficiency in terms of comprehensive energy consumption, heat exchange performance in the cryogenic cold box, and exergy analysis. Adaptability analysis indicated that this Scheme exhibits strong tolerance to variations in feed gas temperature as well as N2 and CO2 content. The ethylene–propane cascade refrigeration process demonstrates significant energy-saving advantages and exhibits robust operational performance.